Study of heterotic potential for important antioxidant and nutritional traits in okra (Abelmoschus esculentus) - DAS, ANJAN; YADAV, RAMESH KUMAR; BHARDWAJ, RAKESH; CHOUDHARY, HARSHWARDHAN; KHADE, YOGESH P (The Indian Journal of Agricultural Sciences, 2022)
Okra (Abelmoschus esculentus) is one of the most nutritious and economic vegetable crop, rich in vitamins, crude fibre, several minerals especially iodine and anti-oxidant compounds. Inspite of its high nutritional value, little efforts have been done in the past for the development of the nutritionally rich F1 hybrids. To address this issue, 10 lines and 3 testers were crossed in line × tester fashion to develop 30 F1 hybrid combinations. All the hybrids, their parents and 1 leading private sector commercial hybrid (Shakti) were evaluated in Randomized Complete Block Design (RCBD) with 3 replications to measure average heterosis, heterobeltiosis, economic heterosis for 8 quality traits consecutively for two seasons (2018–19). Analysis of heterosis over commercial check (Shakti) revealed DOV-92 × Pusa Bhindi-5 as one of the best hybrid for chlorophyll a and b, CUPRAC and moisture (%). Concurrently, VRO-6 × Pusa A-4 was found best for ascorbic acid and sugar content, and DOV-62 × Pusa Bhindi-5 for ascorbic acid and total phenolic content. The check was found superior for total carotenoids content. On the basis of mean yield and quality traits, the best performing hybrid DOV-92 × Pusa Bhindi-5 may be recommended for the large scale evaluation for hybrid, can be released in future for commercial cultivation by the growers.